Cultivation of edible Caulerpa species in Malaysia: current status and future prospects for sustainable aquaculture - Ismail, Mohd Fakhrulddin; Abdullah, Farah Izana; Ismail, Illisriyani; Abd Karim, Murni Marlina; Ramaiya, Shiamala Devi; Benjamin, Mohammad Amil Zulhilmi; Awang, Mohd Azrie; Zakaria, Muta Harah (Springer Science and Business Media B.V., 2024)
The deficiency in the worldwide protein provision from marine capture fisheries has led the Malaysian government to reevaluate its aquaculture approach, prioritising three commodities: seaweed, fish, and marine shrimp. However, comprehensive documentation of the performance of the Malaysian aquaculture sector, particularly in seaweed production, is lacking. Caulerpa (Chlorophyta), a seaweed genus abundantly available in Malaysia, holds the potential to emerge as a primary alternative food source in the future. This paper offers an overview of Caulerpa aquaculture, specifically focusing on C. lentillifera and C. racemosa, covering aspects such as taxonomy, phytomorphology, geographical distribution and habitat, cultivation system, chemical composition, pharmacological properties, and future prospects for sustainable aquaculture. Although the cultivation system has been implemented on a small scale in various districts in Malaysia, it is anticipated to escalate production and productivity due to the substantial demand for Caulerpa spp. both domestically and globally. The cultivation of Caulerpa spp. in Malaysia, in alignment with the National Agrofood Policy 2021–2030 (NAP 2.0), signals a trajectory toward enhancing the nation's food security in aquaculture and meeting the economic requirements for seaweed production.